Volume changes during the motility period of fish spermatozoa: interspecies differences - Bondarenko, Olga; Dzyuba, Borys; Cosson, Jacky; Yamaner, Gunes; Prokopchuk, Galina; Psenicka, Martin; Linhart, Otomar (Theriogenology, 2013)
The aim of this study was to describe spermatozoa volume changes during the motility period of fish species with either osmotic (common carp Cyprinus carpio) or with ionic (sterlet Acipenseri ruthenus and brook trout Salvelinus fontinalis) modes of motility activation. Nephelometry, light microscopy, and spermatocrit methods were used for quantitative assessment of cell volume changes in media of different osmolalities. Significant correlation (R(2) = 0.7341; P < 0.001) between parameter of volume changes measured using nephelometry and light microscopy methods confirmed nephelometry as a sufficiently sensitive method to detect changes of spermatozoa volume. The spermatocrit alteration method resulted in a large proportion of damaged and potentially immotile spermatozoa in media of osmolality less than 150 mOsm/kg in carp and osmolalities from 10 to 300 mOsm/kg in sterlet and brook trout. Therefore, this method is not reliable for assessing spermatozoa swelling in hypotonic solutions, because the integrity of the cells is not fully preserved. Increase in carp spermatozoa (osmotic activation mode) volume occurred during the motility period in hypotonic conditions, but no indications of volume changes were found in sterlet and brook trout spermatozoa (ionic activation mode) associated with environmental osmolality alteration. Accordingly, we conclude that sperm volume changes are differentially involved in the motility activation process. Species-specific differences in spermatozoa volume changes as a response to a hypotonic environment during the motility period are discussed in relation to their potent physiological role.
Keywords: Sperm Motility; Nephelometry and Turbidimetry; Carps; Animals; mužské pohlaví; motilita spermií; Fishes; Microscopy, Electron, Scanning; kapři; zvířata; ryby; Spermatozoa; Male; Trout; spermie; nefelometrie a turbidimetrie; pstruh; mikroskopie elektronová rastrovací